2008
DOI: 10.1186/1472-6874-8-12
|View full text |Cite
|
Sign up to set email alerts
|

Study of knowledge, perception and attitude of adolescent girls towards STIs/HIV, safer sex and sex education: (A cross sectional survey of urban adolescent school girls in South Delhi, India)

Abstract: Background: Sexually Transmitted Infections (STI's), including HIV (Human Immunodeficiency Virus) mainly affects sexually active young people. Young adults aged 15-29 years, account for 32% of AIDS (Acquired Immunodeficiency Syndrome) cases reported in India and the number of young women living with HIV/AIDS is twice that of young men. The aim of the study was to evaluate adolescent school girls' knowledge, perceptions and attitudes towards STIs/HIV and safer sex practice and sex education and to explore their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
78
2
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 10 publications
12
78
2
5
Order By: Relevance
“…Twenty seven adolescents were aware of STIs and the majority of respondents (197 out of 200) had no knowledge about the signs and symptoms of sexually transmitted infections. Similar disturbing findings were given by McManus and Dhar et al (12) Some reported breast pain (7 out of 200) as symptoms of STIs in women.…”
Section: Observations and Discussionsupporting
confidence: 85%
“…Twenty seven adolescents were aware of STIs and the majority of respondents (197 out of 200) had no knowledge about the signs and symptoms of sexually transmitted infections. Similar disturbing findings were given by McManus and Dhar et al (12) Some reported breast pain (7 out of 200) as symptoms of STIs in women.…”
Section: Observations and Discussionsupporting
confidence: 85%
“…The premarital sexual practice is higher when compared to these studies because participants of this study are affected by peer pressure and living separated from their parents where family fear and control is not available [41][42][43].Being adolescent and early adulthood is characterized by different types of risky behaviors, including risky sexual practice, substance abuse and exposure to STIs [19]. Adolescents and college students premarital sex is increasing around the world many of which are risky, unplanned and unprotected [22][23][24]. The mean age of first sexual intercourse of the study participants at which 17.7 years which is higher than the study conducted at Addis Ababa was 12 years for boys and 14 years for girls [38].…”
Section: Discussionmentioning
confidence: 99%
“…While most of the high school students knew that it is spread by unprotected sexual intercourse and can be prevented by safe sexual prac ce 4 , majority of the university students felt that condom can protect them from HIV instead of limi ng sex to single partner and most of them were unaware regarding the mode of transmission of HIV 5 . In a similar Indian study, one third of the respondents felt HIV/AIDS could be cured 6 , likewise one third of Bangladeshi men did not know how to avoid AIDS and very less people knew that HIV can be transmi ed through infected blood and syringes 7 .…”
Section: Introductionmentioning
confidence: 98%